Nutrient fluxes in rural properties in the region semiarid of Brazil - Germana Gomes dos Santos Camelo (2015)
The main sources of nutrients used in agriculture come from the exploitation of mineral reserves of nutrients or fossil fuels, both non-renewable and finite resources. Higher effectiveness in nutrient cycling increases the efficiency of nutrients use, decreasing the dependence on external inputs and increasing the sustainability of the farm system. The objective of present study was to quantify nutrient fluxes in farm systems, enabling the establishment of management strategies to allow P and K cycling in agricultural production systems. The study was conducted at municipality of RedenÃÃo, CearÃ State, Brazil, through interviews with selected farmers, according to the local predominance. The farm was considered as a system composed by processes of human consumption, plant and animal production. Farm systems were classified into typology A and B based on the degree of diversity and interaction between processes. Evaluated material flows were mainly composed by animal food and agricultural inputs and goods and waste outputs in each process. The flow of nutrients was calculated from the material flows and the mineral content in each material, obtained from literature review. Error propagation and nutrient flows representation were carried out using the software STAN. Soil samples were collected to determine P and K stock in a chronosequence of cashew production processes with 0, 6, 7, 8 and 13 years old, with purpose to associate nutrient flows to the variation in nutrient soil stocks over time. Large amounts of P were added to the systems by use of organic fertilizers, resulting in a low efficiency of using of this nutrient. The production of cassava proved main drain system K, and therefore the survey and analysis of waste produced in the cassava processing may be the next step to identify strategies to enable K cycling. It was not possible to identify any nutrient cycling in the evaluated systems. The different degree of diversity and interactions between activities were restricted to flows from crop to animal production.